Қорақалпоғистон шороитида эчкилар (capra hircus l.) гельминтлари тур таркиби ва уларнинг организмда тақсимланиши (SCIENCE and SOCIETY, 2023)
It was revealed that 29 species of helminths belonging to 21 genera, 14 families, 9 families, 3 classes and 2 species parasitize goats in the conditions of Karakalpakstan. The largest number of identified helminths, i.e. 19 species belong to the class of nematodes (66%), 7 species to the class of cestodes (24%) and 3 species to the class of trematodes (10%).